Analysis of Metacognition Ability to Solve Mathematics Problem - Fani Yunida Anggraheni; Kismiantini Kismiantini; Ariyadi Wijaya (Southeast Asian Mathematics Education Journal, 2023)
In this study, two components of metacognition were examined, namely metacognitive knowledge and metacognitive skills. This study aims to analyse the students’ metacognitive abilities based on predetermined indicators, by looking at the relationship between the performance of metacognition knowledge and metacognition skill. The study discovers that the students with low, medium, and high scores perform differently. The conclusion is that students who have metacognition knowledge do not necessarily have metacognition skills or abilities.